Oligometastasis scoring system for predicting survival of patients with colorectal liver metastasis after hepatectomy. Issue 5 (30th June 2021) - Inoue, Hiroyuki; Kawaguchi, Tsutomu; Ikoma, Hisashi; Morimura, Ryo; Yamamoto, Yusuke; Ochiai, Toshiya; Shimizu, Hiroki; Arita, Tomohiro; Konishi, Hirotaka; Shiozaki, Atsushi; Kuriu, Yoshiaki; Kubota, Takeshi; et al.
Abstract: Background: Oligometastasis, the presence of a small number of resectable metastatic tumors, usually has favorable outcomes. Here we examined whether the novel oligometastatic score (OLGS), which divides the number of colorectal liver metastases (CRLMs) by the time from colorectal resection to liver recurrence, better predicts CRLM patient survival than the commonly used clinical risk score. Methods: A total of 143 patients who underwent curative hepatectomy for CRLMs between 2007 and 2018 were analyzed. We investigated their clinical characteristics and outcomes using OLGS. Results: Of the 143 CRLM patients, 70 had synchronous CRLMs and 73 had metachronous CRLMs. Patients with metachronous CRLMs were divided into OLGS‐low ( n = 59) and OLGS‐high ( n = 14) subgroups. The 5‐year overall survival (OS) rates after hepatectomy differed significantly between the subgroups ( p < .001). In the multivariate Cox model, a high OLGS was an independent predictor of 5‐year OS ( p < .001), and the hazard ratio (HR) of the OLGS‐high group (HR = 7.171) was higher than that of the high clinical risk score group (HR = 4.337). Conclusion: The OLGS, a simple and handy scoring system, better predicts the 5‐year OS of patients with CRLMs after hepatectomy and warrants prospective validation.